2010
DOI: 10.1073/pnas.1006662107
|View full text |Cite
|
Sign up to set email alerts
|

Design of a potent CD1d-binding NKT cell ligand as a vaccine adjuvant

Abstract: The glycolipid α-galactosylceramide (α-GalCer) has been shown to bind CD1d molecules to activate invariant natural killer T (iNKT) cells, and subsequently induce activation of various immune-competent cells, including dendritic cells, thereby providing a significant adjuvant effect for various vaccines. However, in phase I clinical trials, α-GalCer was shown to display only marginal biological activity. In our search for a glycolipid that can exert more potent stimulatory activity against iNKT cells and dendri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

7
204
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 166 publications
(212 citation statements)
references
References 32 publications
7
204
0
1
Order By: Relevance
“…1). Among them, 17 glycolipids studied by Li et al suggested that the 7DW8-5 had the greatest capacity for induction of IFN-γ production in human NKT cells and binding to CD1d (24). In this study, five glycolipids (C34, C30, C35, C36, and C37) were also evaluated and compared to 17 previously reported phenyl glycolipids.…”
Section: Resultsmentioning
confidence: 99%
“…1). Among them, 17 glycolipids studied by Li et al suggested that the 7DW8-5 had the greatest capacity for induction of IFN-γ production in human NKT cells and binding to CD1d (24). In this study, five glycolipids (C34, C30, C35, C36, and C37) were also evaluated and compared to 17 previously reported phenyl glycolipids.…”
Section: Resultsmentioning
confidence: 99%
“…Like EF77, 7DW8-5 also has a modification in the acyl group. The length of the chain has been shortened to 11 carbons and a parafluor-phenyl group has been added (19,20). The rationale behind those different modifications is that changes in the lipid moiety would be expected to mainly influence the lipid interaction with CD1d, whereas changes in the galactose moiety and linkage can affect interaction with CD1d; the TCR and they could confer resistance to endoglycosidases upon injection into mice and thus could increase the half-life in serum.…”
Section: Resultsmentioning
confidence: 99%
“…16 α-GalCer derivatives with different aryl moieties at the acyl chain terminus have exhibited remarkable activity. 19,20 These analogues exhibited strong iNKT stimulation with Th1 bias. 20,21 According to Wu et al, their docking models revealed additional hydrogen bonding between the phenyl/aryl ring of the fatty acyl chain and the aromatic amino acid residues present on the wall of the A′ pocket in the CD1d hydrophobic groove.…”
mentioning
confidence: 99%
“…19,20 These analogues exhibited strong iNKT stimulation with Th1 bias. 20,21 According to Wu et al, their docking models revealed additional hydrogen bonding between the phenyl/aryl ring of the fatty acyl chain and the aromatic amino acid residues present on the wall of the A′ pocket in the CD1d hydrophobic groove. 22 One such analogue (7DW8−5) from the same structural class exhibited superior adjuvant activity compared to that of α-GalCer in HIV and malaria vaccines in mice.…”
mentioning
confidence: 99%
See 1 more Smart Citation